ANALYSIS OF CENTRAL JAVA TOURISM RETRIBUTION IN 2015-2019 - Nina Setiarini; Rian Destiningsih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the tourism retribution of Central Java in 2015-2019. This quantitative study uses survey as data collection method. Data analysis uses panel data regression, there are several methods for estimating the regression model, while to find the best estimation model used Chow test, Hausman test and Lagrange Multiplier Test, Classical Assumption Test used to determine the collinearity, heteroscedasticity, and autocorrelation in the regression estimation, and Statistical test to determine significance. The result of the analysis reveal that the number of tourism objects has a positive and significant influence on tourism levies, while number of tourists has no influence on tourism levies, number of hotels has a negative and significant influence on tourism levies. Furthermore, variable of number of tourism objects, number of tourists, as well as number of hotels affect the tourism levies in Central Java in 2015-2019 simultaneously.